What are the complications and emerging strategies for preventing depression following traumatic brain injury?. (3rd June 2017) - Jones, Melissa; Acion, Laura; Jorge, Ricardo E.
ABSTRACT: Introduction : Depression is a common and disabling complication of traumatic brain injury (TBI). The high rates of post-TBI depression (PTBID) make this condition an important candidate for selective preventive interventions. Areas covered : The authors recently reported on the efficacy of sertraline, a selective serotonin reuptake inhibitor (SSRI), for the prevention of new cases of depression in the first six months after TBI. The authors review this and other studies on preventive strategies in PTBID as ascertained from a PubMed and citation search. The potential complications and barriers to the implementation of pharmacological prevention in patients with TBI are also discussed. Expert commentary : The prevention of depression in patients with TBI has received little attention relative to other medical conditions. Future studies are needed to confirm the benefit of SSRIs and investigate other pharmacological and non-pharmacological interventions, including in special groups of patients at greater risk of developing PTBID.